Family Against the Odds: The Psychological Impact of Family Separation on Refugee Men Living in the United Kingdom - Dafni Katsampa; Christina Curry; Ella Weldon; Haben Ghezai; Patrick Nyikavaranda; Vasiliki Stamatopoulou; David Chapman (Social Sciences)
Refugees face post-migration stressors during resettlement in host countries, including forced separation from loved ones. This qualitative study aimed to examine the impact of family separation on refugee men living in the United Kingdom. Data were collected through in-depth interviews and analysed following the Interpretative Phenomenological Analysis framework. Participants described the emotional burden of family separation, alongside a perceived responsibility to support their families practically, emotionally, and financially. Men shared experiences of powerlessness, discrimination, and acculturation in the UK, and associated their experiences with time and context. Participants’ stories were embedded in their intersectional identities of masculinity, race, sexuality, religion, and migration status. Policymakers should consider the unique challenges male refugees separated from their families face in the UK in order to implement positive changes in the asylum system. Clinicians working with refugees and asylum-seekers should inform their assessment, formulation, and intervention approaches.